Boron-Doped Graphene Quantum Dots (BGQDs) from Spent Coffee Ground for Glucose Sensor. (17th December 2022) - Hadish, Filimon; Chiang, Meng-Hsuan; Hsieh, Yi-Fang; Wu, Shao-Yu; Jou, Shyankay
Abstract : We have prepared graphene quantum dots (GQDs) and boron-doped GQDs (BGQDs) utilizing spent coffee grounds (SCGs) via a simple one-step hydrothermal process for glucose sensor application. FTIR and XPS characterizations reveal that the boron atoms have been successfully doped into graphene structures. BGQDs on glassy carbon electrode (GCE) in PBS were found to be two times as active compared to GCE/GQDs electrodes. The significant difference in electrochemical activity shown by BGQDs is evidence that boron from boric acid was doped into the graphene dominion. The generation of boronic acid groups on the boron-doped graphene quantum dots (BGQDs) surfaces facilitates the application of GQDs as a new photoluminescence (PL) probe for label-free glucose sensing. The photoluminescence of developed GQDs showed a linear response to glucose over a concentration range of 5–45 mM with a limit of detection of 12.45 mM whereas BGQDs biosensor was found to exhibit a higher sensitivity over the same concentration range with limit of detection of 3.23 mM towards glucose sensing. These results demonstrate that the synthesized BGQD has a promising potential in electrochemical activity and efficient to the PL enhancement mechanism determination of glucose.